The cytotoxic role of RREB1, ZIP3 zinc transporter, and zinc in human pancreatic adenocarcinoma - Franklin, Renty B (Landes Bioscience, 2014)
Pancreatic cancer (ductal adenocarcinoma) remains a deadly cancer with ~85% mortality, and a 5-year survival rate of ~6% or less for the past 30 years. The factors and events associated with the development of pancreatic cancer are poorly identified. As such, effective biomarkers for early detection of malignancy are lacking. Efficacious chemotherapy once the cancer is identified does not exist. Recent clinical studies have revealed that the zinc levels are consistently and markedly decreased in adenocarcinoma as compared with normal/benign pancreatic tissue. The decreased zinc is exhibited in well-differentiated malignancy and in progressing malignancy, and also exists throughout the development of PanIN. Concurrent with the decrease in zinc, RREB1 transcription factor and ZIP3 zinc uptake transporter are downregulated. Thus, a RREB1/ZIP3/Zinc transformation appears to be an early event in the development of pancreatic cancer. We propose that this transformation is necessary to prevent the accumulation of high cellular zinc levels, which result in cytotoxic effects on the developing malignant cells. This report now demonstrates that exposure of Panc1 cells to physiological concentrations of zinc that result in increased zinc uptake and accumulation also inhibits cell proliferation. The study further shows that ZIP3 is the important transporter required for the accumulation of zinc and its inhibition of proliferation. RREB1 is identified as the positive regulator of ZIP3 expression. Therefore, the pathway of RREB1/ZIP3/Zinc and its downregulation during oncogenesis exist to prevent the accumulation of cytotoxic levels of zinc during the development and progression of the malignant cells in pancreatic adenocarcinoma.